Nave industrial Arruga Movi Studio, Sant Just Desvern, Barcelona - Ferrater, Carlos; Guibernau, Joan (1998)
Número dedicado a las obras finalistas del Premio FAD de arquitectura e interiorismo 1998
Keywords: PREMIOS FAD; ESTUDIOS DE CINE; BARCELONA; ESPAÑA